PENGARUH EKSPOR MINYAK ANGOLA KE INDUSTRI CINA PASCA MASUKNYA ANGOLA KE OPEC TAHUN 2007 - Nina Oktapiani Sembiring Kembaren; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study describes China's response to the entry of Angola to OPEC in January 2007. Following the entry of Angola OPEC to be a threat, fear and even fears for China over oil supply that affect the development of Chinese industry is growing rapidly. OPEC exports and reduction rules can threaten Angola's oil exports to China. So, researchers ask a question what effect after entry of Angola's oil exports to OPEC Angola 2007. These problems make China take some action to secure the supply of oil to the country such as cooperation, oil-backed loan system, Angola Model, going out strategy and development assistance. These actions are expected to have an impact on FDI and GDP growth in both countries.This study used a qualitative research method, the research library research techniques are sourced from books, journals, theses, websites, articles, and official reports to the type of research is the analysis. The author uses the theory of supply and demand as well as the relationship of sustainability in both countries.From the research literature by the author can be concluded that after the entry of Angola to OPEC in 2007 impacted the Angolan oil exports to China from January 2007. The increase in activity is due to some action taken China as loans assistance (oil-backed loans) where the return or Angola debt payments by oil, cooperation in several sectors, especially infrastructure development in post-war Angola 27 in the country thereby increasing FDI and GDP growth and lead to sustainability relationships in both countries. This relationship confirms that the entry of sustainability Angola OPEC to have a positive impact on the development of China industries as China lock Angola's oil exports by which promises actions with Angola.Keywords : Oil, FDI, GDP, Demand, Supply, Sustainability